Savaxay and the language of kinship in Batanic communities - Gallego, Ma. Kristina S. (Social Science Diliman: A Philippine Journal of Society and Change, 2017)
Based on kinship terminologies collected for Batanic languages, this study reconstructs the Proto-Batanic kinship system and traces its transformations in present-day daughter communities. Since speakers of Batanic languages have maintained close contact among each other, the groups exhibit significant similarities not only in linguistic structure but also in certain cultural aspects such as kinship. All Batanic communities follow a lineal type of kinship(also known as Eskimo type), which is a retention of the ancestral Batanic kinship system. This is a departure from the generation type (also known as Hawaiian type) reconstructed for Proto-Philippines and Proto-Malayo-Polynesian. This development is analyzed as a reflection of changes in the behavior of the speakers, particularly in terms of rule of residence. Moreover,the physical house is seen as a reproduction of kinship relations in Batanic communities,where it serves as the primary locus of activities, rituals, and traditions that relate to kinship. Despite significant transformations in the kinship system of Batanic communities since their descent from Proto-Philippines, cultural features, particularly the value structure of Filipino communities, persist to this day. KEYWORDS: kinship, Batanes, ethnolinguistics, historical linguistics, language, culture